MENGUBAH NETRALITAS BIROKRASI KLASIK MENJADI NETRALITAS BIROKRASI BARU - Dwiyanto Indiahono (Badan Kepegawaian Negara | The National Civil Service Agency, 2009)
Classic neutrality principles of bureaucracy which put down bureaucracy as pure administrator of implementor, apolitic and has low accountability have to be changed become new neutrality principles of bureaucracy. New neutrality principles of bureaucracy want bureaucracy can act as critical administrator and implementor, politic (join in accommodating and submitting public aspiration) and has high accountability (by developing open accountability). New neutrality principles of bureaucracy can be applied if there are supporter system, like: political system which is egaliter and responsive; elite of bureaucracy and politic committing to behave egaliter, responsive and supporting the betterness change; and also education of politics that giving position citizen as most sovereign institution. Keywords: new neutrality principles of bureaucracy, bureaucracy, political system and politic education.